Pengembangan Media Pembelajaran Pemeliharaan Kelistrikan Kendaraan Ringan Berbasis Masalah untuk Meningkatkan Kemampuan Berpikir Tingkat Tinggi - Ridho Saputro; Gunadi Gunadi (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to develop problem-based learning media for the subject of light vehicle electrical maintenance to enhance higher-order thinking skills and determine the feasibility and effectiveness of the developed media. This research follows the ADDIE development model, which consists of five stages: analyze (needs analysis, student analysis, curriculum analysis, and concept mapping), design (designing body electrical media with a Diagnostic Trouble Box/DTB and learning instruments), develop (validation by experts, revisions, and readability testing), implement (application in learning), and evaluate (overall evaluation). The study involved 64 twelfth-grade students of the Light Vehicle Engineering (TKR) program at SMK Negeri 2 Yogyakarta, divided into an experimental group (32 students) and a control group (32 students). Research instruments included teaching modules, student worksheets (LKPD), learning materials, and a media user guide. Data were collected using validation sheets, media feasibility sheets, and higher-order thinking skills tests. The field trial was conducted using a quasi-experimental method with a pretest-posttest control group design, and effectiveness was analyzed using a t-test. The results indicate that learning using DTB-based media with a problem-based approach effectively enhances students' higher-order thinking skills. The media was rated "highly feasible" by experts and received a "very good" response from students. Its effectiveness in improving higher-order thinking skills falls into the "high" category.